2017
DOI: 10.1002/jor.23521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local vanadium delivery on diabetic fracture healing

Abstract: This study evaluated the effect of local vanadyl acetylacetonate (VAC), an insulin mimetic agent, upon the early and late parameters of fracture healing in rats using a standard femur fracture model. Mechanical testing, and radiographic scoring were performed, as well as histomorphometry, including percent bone, percent cartilage, and osteoclast numbers. Fractures treated with local 1.5 mg/kg VAC possessed significantly increased mechanical properties compared to controls at 6 weeks post-fracture, including in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
(123 reference statements)
0
9
0
1
Order By: Relevance
“…Research from Paglia et al and Ippolito et al has shown that a different organic vanadium salt, Vanadyl acetylacetonate (VAC), has a positive effect in promoting chondrogenic wound healing closure, most likely via increasing angiogenesis [18][19][20]. It was previously described that BMOV could enhance collateral blood flow in a rat model of peripheral vascular disease and increase the diameter of cerebral collateral in rats [9,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from Paglia et al and Ippolito et al has shown that a different organic vanadium salt, Vanadyl acetylacetonate (VAC), has a positive effect in promoting chondrogenic wound healing closure, most likely via increasing angiogenesis [18][19][20]. It was previously described that BMOV could enhance collateral blood flow in a rat model of peripheral vascular disease and increase the diameter of cerebral collateral in rats [9,23].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that different organic vanadium salts have a positive effect in promoting wound healing closure, most likely via increasing angiogenesis. Vanadyl acetylacetonate (VAC) has been shown to increase chondrogenesis and angiogenesis in fracture healing in rats [18][19][20]. Based on these findings we hypothesized that BMOV would promote wound closure in vivo in C57BL/6JRj mice.…”
Section: Introductionmentioning
confidence: 99%
“…The diabetes-prone BB-Wistar rat is an animal model with a close homology to human type 1 DM pathology. 19,23 BB-Wistar rats were obtained from Health Canada Animal Research Division (Ottowa, Canada), housed under pathogen-free conditions, and fed ad libitum. Research protocols were approved by the Rutgers Institutional Animal Care and Use Committee.…”
Section: Animal Modelmentioning
confidence: 99%
“…Furthermore, this murine model causes severe cytotoxic effects related with the transport capacity of glucose through the glucose transporters GLUT-2 and GLUT-1 in the pancreas, liver, kidney, and brain, producing tissue-specific cell death and structural and metabolic changes. All these issues complicate the correct anti-diabetic evaluation of vanadium compounds using this model [276][277][278][279]. The hypoglycemic potential of various vanadium compounds has also been examined in models that present features similar to those observed in types 1 and 2 diabetes mellitus.…”
Section: Vanadium Anti-diabetic Compounds In Animal and Human Modelsmentioning
confidence: 99%